Analysis of uniaxially loaded short round-ended concrete-filled steel tubular beam-columns. (15th February 2020) - Patel, Vipulkumar Ishvarbhai
Highlights: A fiber model for uniaxially loaded RCFST beam-columns is developed. The local and post-local buckling of steel flange is considered. The analysis procedure for load-moment diagram is presented. The assessment of Eurocode 4 for the design of RCFST beam-column is given. Abstract: Round-ended concrete-filled steel tubular (RCFST) columns exhibit low resistance to running water, strong y -axis bending strength and aesthetic appearance for their use in bridge piers. However, the behavior of RCFST beam-columns under uniaxial loading has not been studied numerically. This paper describes the computational simulation and design of uniaxially compressed short RCFST beam-columns. The nonlinear simulation is based on the numerical fiber-based methodology. The flange local and post-local stability in terms of outward buckling of the flat plate and circular-rectangular concrete confinement are considered in the fiber-based simulation. The simulation procedures for generating the load-strain responses, moment-curvature curves, and nonlinear strength envelopes are described. The computed axial capacity, ultimate bending strength and load-strain performance of short RCFST beam-columns are assessed against the independent experimental results. The statistical results reveal the accuracy of the fiber-based simulation for exploring the compression and bending behavior of short RCFST beam-columns. The parametric analysis is conducted using the fiber-based model to examine the local buckling, bending axis, aspect ratio, and material strength influence on the performance of uniaxially compressed RCFST short beam-columns. The design of eccentrically loaded short beam-columns based on Eurocode 4 provisions is described.